2010
DOI: 10.1212/wnl.0b013e3181cbcd48
|View full text |Cite
|
Sign up to set email alerts
|

The 5-year direct medical cost of neonatal and childhood stroke in a population-based cohort

Abstract: Background: Despite increasing awareness of the long-term impact of pediatric stroke, there are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 33 publications
4
63
0
1
Order By: Relevance
“…Daily searches of the local accident and emergency attendance register. 4. Monthly computerized searches of general practitioner diagnostic coding and hospital discharge codes.…”
Section: December 2012mentioning
confidence: 99%
See 2 more Smart Citations
“…Daily searches of the local accident and emergency attendance register. 4. Monthly computerized searches of general practitioner diagnostic coding and hospital discharge codes.…”
Section: December 2012mentioning
confidence: 99%
“…Although not a health care cost, long-term institutionalization has been shown to be a major component of overall costs after stroke. 4 Third, our overall costs are only applicable to the United Kingdom and possibly to similar health care systems in which a high proportion of patients with TIA and minor stroke are investigated and treated in the outpatient setting. Our predictors of cost, however, are more likely to be generalizable to other health care settings.…”
Section: December 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] However, pediatric stroke remains under-recognized among health care providers; a lack of evidence-based treatment and management guidelines specific to the pediatric population further complicates this problem. 7,8 This represents a critical health care problem, given the potential cost to society in terms of life-years of disability and life-years lost in the face of increasing incidence of acute ischemic arterial infarction of children. 6,7,9,10 Recent studies support infarct volume quantification as a potential tool in the pediatric population for predicting clinical outcome.…”
mentioning
confidence: 99%
“…7,8 This represents a critical health care problem, given the potential cost to society in terms of life-years of disability and life-years lost in the face of increasing incidence of acute ischemic arterial infarction of children. 6,7,9,10 Recent studies support infarct volume quantification as a potential tool in the pediatric population for predicting clinical outcome. [11][12][13] For example, Ganesan et al 14 observed that infarcts of Ͼ10% parenchymal volume on T2-weighted imaging were associated with poor outcomes.…”
mentioning
confidence: 99%